BRIDGING THE GAP: NURSE-LED INITIATIVES FOR MITIGATING SOCIAL DETERMINANTS OF HEALTH DISPARITIES - Bandar Abdullatif Alghamdi, Osamah Zaid Jazaa Almutairi,Majed Ghanem Aldosari, Turki Fahad Al Dawsari,Abdullah Hamd Hamdan Al Hamdan,Mohammed Jawad Alhelal, Mustafa Mohammed Alhelal, Amna Nouri Alfashkhi, ,; Fawzi Mohamad Ali Almosa, Mohammed Hussien Almukalaf, Abdulrahman Hamad Alhamad, Mahdi Jawad Alhelal, Enad Bdr Alsuwailem,Mohammed Mossa Alherz,Ali Mohammed Alhassan, (Chelonian Research Foundation, 2022)
Nurses have the potential to play a crucial role in advancing health care fairness in the next ten years by assuming more responsibilities, working in novel environments with creative approaches, and collaborating with communities and other sectors. However, the ability of nurses to assist individuals and communities in leading healthier lifestyles can only be achieved if the obstacles preventing them from using their education and training to the fullest degree are eliminated. In order to achieve this objective, it will be imperative to modify laws pertaining to the range of activities that healthcare professionals are authorized to do, as well as policies related to public health and the healthcare system. Additionally, state laws concerning the use of standing orders and the regulations governing payment for Medicare and other payers will need to be revised. The next generation of nurses will practice and lead in an environment that will undergo significant transformations due to major upheavals in both society and health care. In order to attain complete health care equality, nursing schools must prioritize the development of nurses who possess the ability to address the socioeconomic determinants of health and provide treatment that is tailored to individuals' circumstances, independent of their practice environment. Keywords: Social determinates, nurse, healthcare system, review.